There was less self-critique among basic than in clinical science articles in three rheumatology journals - (:unkn) unknown (ELSEVIER SCIENCE INC, 2014)
Objectives: There is concern that self-critique with authors acknowledging limitations of their work is not given due importance in scientific articles. We had the impression that this was more true for articles in basic compared with clinical science. We thus surveyed for the presence of self-critique in the discussion sections of the original articles in three rheumatology journals with attention to differences between the basic and the clinical science articles. Study Design and Setting: The discussion sections of the original articles in January, May, and September 2012 issues of Annals of the Rheumatic Diseases, Arthritis and Rheumatism, and Rheumatology (Oxford) were surveyed (n = 223) after classifying each article as mainly related to clinical or basic science. The discussion sections were electronically scanned by two observers for the presence of the root word limit or its derivatives who also read each discussion section for the presence of any limitations otherwise voiced. Results: A limitation discussion in any form was present in only 19 (20.2%) or 29 (30.1%) of 94 basic science vs. 95 (73.6%) or 107 (82.3%) of 129 clinical science articles (P < 0.0001 for either observer). Conclusion: Self-critique, especially lacking in basic science articles, should be given due attention. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Self-critique; Limitations; Acknowledging limitations; Basic science; Clinical science; Article discussion sections; LIMITATIONS